Controversies in Education: Orthodoxy and Heresy in Policy and Practice - Proctor, Helen (Springer, 2016)
This book is the outcome of a colloquium series organized by The University of Sydney in which leading and emerging researchers were invited to name what they took to be the deep flaws at the heart of contemporary educational and policy and practice in Australia and globally — to voice their potentially ‘heretical’ views on what most urgently needs to be done. The chapters in this collection are paired to offer two takes on each topic, from supplementing to critiquing to countering and most points in between. The issues addressed in this volume include: the place of education in national and international marketplaces, mass testing and standardisation, the future of ‘multiculturalism’ in schools, the public funding of private schools, the complicated relationship between evidence and policy and the shifting politics of inequality. This book is based on the idea that recognising deep disagreements on big issues is a necessary accompaniment to imagining and developing productive ways forward.